Exclusive breastfeeding at three months and infant sleep-wake behaviors at two weeks, three and six months - Figueiredo, Bárbara (2017)
This study assessed infant sleep-wake behavior at two weeks, three and six months as function of feeding method at three months (exclusively breastfed, partially breastfed, and exclusively formula fed infants). Mothers of 163 first-born, full-term, normal birth weight, healthy infants completed socio-demographic, depression, anxiety, and infant sleep-wake behavior measures. No effects were found for sleep arrangements, depression or anxiety, on feeding methods and sleep-wake behavior at three months. At two weeks exclusively breastfed infants at three months spent more hours sleeping and less hours awake during the 24-h period than partially breastfed infants. At three months, exclusively breastfed infants had a shorter of the longest sleep period at night than exclusively formula fed infants. At six months, exclusively breastfed infants at three months spent more hours awake at night than partially breastfed infants, awake more at night than exclusively formula fed infants, and had a shorter sleep period at night than partially breastfed and exclusively formula fed infants. This study showed differences in sleep-wake behaviors at two weeks, three and six months, when exclusively breastfed infants are compared with partially breastfed and exclusively formula fed infants at three months, while no effects were found for sleep arrangements, depression or anxiety.